2007
DOI: 10.2478/v10044-008-0005-5
|View full text |Cite
|
Sign up to set email alerts
|

Can economic stress affect secondary sex ratio in Poland?

Abstract: The ratio of male to female births described as the male proportion is expected to be about 1.06. The secondary sex ratio can be influenced by various stresses experienced by parents (e.g., parents' exposure to chemical and physical pollution, natural phenomena, wars and economic crises). The seminal study in this field speculated that fewer goods and services than needed or desired might sufficiently stress human populations to lower the secondary sex ratio. The main purpose of this study is to examine the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…18 of responses to acute environmental stress is the modification of the natural sex ratio of the offspring, which manifests itself in a decrease in the SRB value. 26 Therefore, the index of male-to-female live births is considered a "measure" of adverse environmental conditions caused by ecological, economic, or political factors, etc. Studies of contemporary and historical populations have shown that wars, armed conflicts and economic crises can be sources of stress for the human body, including that of a pregnant woman.…”
Section: Słowa Kluczowementioning
confidence: 99%
“…18 of responses to acute environmental stress is the modification of the natural sex ratio of the offspring, which manifests itself in a decrease in the SRB value. 26 Therefore, the index of male-to-female live births is considered a "measure" of adverse environmental conditions caused by ecological, economic, or political factors, etc. Studies of contemporary and historical populations have shown that wars, armed conflicts and economic crises can be sources of stress for the human body, including that of a pregnant woman.…”
Section: Słowa Kluczowementioning
confidence: 99%
“… Helle et al (2009) found a non-significant relationship between SRB and percentage change in real gross domestic product (GDP) in Finland in 1865–2003. Another study showed no relationship between consumption and SRB in Poland when using annual data for the period 1956–2005 ( Żądzińska et al , 2007 ), while a later investigation conducted by the same researchers using quarterly data for the period 1995–2007 reported a reduction in SRB in Poland four quarters after the occurrence of economic decline ( Żądzińska et al , 2011 ). An integrative review article suggested that the association between economic stress and SRB presented in former research remained largely speculative and acknowledged the needs for more research on this topic ( Margerison Zilko, 2010 ).…”
Section: Introductionmentioning
confidence: 96%
“…Helle et al [ 15 ] likewise found a negative, yet smaller, association between GDP and the SRB in Finland between 1865 and 2003, controlling for a range of additional contextual influences on the SRB. However, a time series analysis examining the links between consumption data and the SRB for Poland between 1956 and 2005, Żądzińska et al [ 18 ], found no association. A positive association between economic conditions and the SRB appeared in Cuba after the economic collapse in the early 1990s [ 19 ].…”
Section: Introductionmentioning
confidence: 99%